TUJUAN OTONOMI DAERAH DAN ALASAN PEMEKARAN WILAYAH (Universitas PGRI Sumatera Barat, 2013)
Regional autonomy is the right, authority, and duties of the autonomous regions to organize and manage their own affairs and interests of local communities in accordance with the legislation. The purpose of regional autonomy under Law no. 5 1975 is to allow the relevant area to control and manage their own households to improve the effectiveness and efficiency of government administration in the context of service to the community and implementation. Increase the effectiveness and efficiency of regional government, especially in the implementation of development and service to the community and to improve pembinanan political stability and national unity.